Comparison of five presbyopia-correcting intraocular lenses: optical-bench assessment with visual-quality simulation - Łabuz, Grzegorz; Yan, Weijia; Baur, Isabella; Khoramnia, Ramin; Auffarth, Gerd U. (Journal of Clinical Medicine, 2023)
Presbyopia correction through implantation of a trifocal intraocular lens (IOL) is a modality offered to both cataract and refractive-lens exchange patients. To maximize postoperative satisfaction, IOL selection needs to be made based on patients’ requirements aligned with the available technology. Five Trifocal IOLs were assessed in this study, and their differentiating features were identified: Triumf POD L GF, AT Lisa Tri, Tecnis Synergy, AcrySof IQ PanOptix, and Acriva Trinova Pro C. The optical quality was assessed using the modulation-transfer-function principle. Simulated defocus curves were derived from a non-linear formula. Far-focus simulated visual acuity (simVA) was 0.03 logMAR or better for all the studied IOLs, showing minimal differences. However, each IOL’s intermediate focus position differed across a range from 61 cm to 80 cm; and for the near focus, it was 36 cm to 44 cm. Triumf demonstrated improved intermediate point at the expense of the near focus resulting in a lower predicted near VA. PanOptix exhibited the shortest range of vision without a clear distinction between intermediate and near-point. The remaining lenses presented three foci of comparable optical quality and, thus, simVA performance. Each model, however, revealed a different aperture-change response. Trinova function improved at intermediate but was worse at near for larger pupils. The opposite was observed for AT Lisa. Synergy’s optical quality change was predominantly associated with lower pupil diameter. In conclusion, the trifocal IOLs can be differentiated according to their secondary-foci position, light-energy distribution, and pupil-size-related behavior. The observed differences may translate directly into a clinical effect showing that the trifocal IOLs vary in their ability to deliver optimal vision at different distances, with some providing improved intermediate while others favor reading distance. The knowledge gained through this objective testing can support IOL selection, postoperative patient counselling and increase the chance of spectacle independence after surgery.